Gapless quantum spin liquid ground state in the two-dimensional spin-1/2 triangular antiferromagnet YbMgGaO4 - Li, Yuesheng; Liao, Haijun; Zhang, Zhen; Li, Shiyan; Jin, Feng; Ling, Langsheng; Zhang, Lei; Zou, Youming; Pi, Li; Yang, Zhaorong; Wang, Junfeng; Wu, Zhonghua; et al. (Scientific reports, 2015)
Quantum spin liquid (QSL) is a novel state of matter which refuses the conventional spin freezing even at 0 K. Experimentally searching for the structurally perfect candidates is a big challenge in condensed matter physics. Here we report the successful synthesis of a new spin-1/2 triangular antiferromagnet YbMgGaO 4 with sy m metry. The compound with an ideal two-dimensional and spatial isotropic magnetic triangular-lattice has no site-mixing magnetic defects and no antisymmetric Dzyaloshinsky-Moriya (DM) interactions. No spin freezing down to 60 mK (despite θ w ~ −4 K), the power-law temperature dependence of heat capacity and nonzero susceptibility at low temperatures suggest that YbMgGaO 4 is a promising gapless (≤|θ w |/100) QSL candidate. The residual spin entropy, which is accurately determined with a non-magnetic reference LuMgGaO 4 , approaches zero (<0.6%). This indicates that the possible QSL ground state (GS) of the frustrated spin system has been experimentally achieved at the lowest measurement temperatures.